2016
DOI: 10.1016/j.ebiom.2016.08.030
|View full text |Cite
|
Sign up to set email alerts
|

A Magnetoencephalographic (MEG) Study of Gulf War Illness (GWI)

Abstract: BackgroundGulf War Illness (GWI) has affected many Gulf War veterans. It involves several organs, most notably the brain. Neurological-cognitive-mood-related symptoms frequently dominate and are at the root of chronic ill-health and disability in GWI. Here we investigated the neural mechanisms underlying brain dysfunction in GWI in the absence of mental health disorders.MethodsEighty-six veterans completed diagnostic interviews to establish the presence of GWI and assess mental health status. Participants diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…These correlations have proved powerful in successfully discriminating various brain diseases (Georgopoulos et al, 2007), including posttraumatic stress disorder (PTSD) (Georgopoulos et al, 2010, Engdahl et al, 2010), and in identifying neural correlates of resilience to trauma (James et al, 2013), of posttraumatic growth (Anders et al, 2015), and of measures of psychopathology (James et al, 2015). More importantly, in a recent study of MEG patterns in GWI (Engdahl et al, 2016) we found synchronous crosscorrelations differed significantly between controls and GWI patients and could classify successfully (> 93% correctly) control and GWI participants. These findings provided the framework for this study, which investigated more specifically the relations between these correlations and specific GWI symptomatology.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…These correlations have proved powerful in successfully discriminating various brain diseases (Georgopoulos et al, 2007), including posttraumatic stress disorder (PTSD) (Georgopoulos et al, 2010, Engdahl et al, 2010), and in identifying neural correlates of resilience to trauma (James et al, 2013), of posttraumatic growth (Anders et al, 2015), and of measures of psychopathology (James et al, 2015). More importantly, in a recent study of MEG patterns in GWI (Engdahl et al, 2016) we found synchronous crosscorrelations differed significantly between controls and GWI patients and could classify successfully (> 93% correctly) control and GWI participants. These findings provided the framework for this study, which investigated more specifically the relations between these correlations and specific GWI symptomatology.…”
Section: Introductionmentioning
confidence: 59%
“…Cognitively healthy individuals display remarkably similar patterns of neural synchronicity (Langheim, 2006), whereas alterations in neural synchrony have been associated with several neuropsychiatric disorders (Engdahl et al, 2010, Georgopoulos et al, 2007, Georgopoulos et al, 2010, James et al, 2013, 2015; Uhlhaas and Singer, 2006). We have recently demonstrated that GWI is also associated with aberrant synchronicity affecting cortical areas and the cerebellum (Engdahl et al, 2016). Our working hypothesis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Many symptoms of GWI involve the central nervous system; consequently, several studies have investigated brain structure and function as it relates to GWI, with mixed findings ( White et al, 2016 ). We have recently identified functional ( Engdahl et al, 2016 ) and structural ( Christova et al, 2017 ) brain anomalies in GWI, both of which prominently involved subcortical regions. For example, compared to healthy control veterans, veterans with GWI showed an average of 10.4% reduction in cerebellar volume and 2 × the rate of reduction of cerebellar gray matter volume with age (− 14%/decade in GWI vs. − 6.9%/decade in controls).…”
Section: Introductionmentioning
confidence: 99%
“…A prior report in EBioMedicine by Georgopoulos and colleagues (Georgopoulos et al, 2015) provided insight into a basis for a genetic/immune role in GWI by showing that higher counts for six Class II human leukocyte antigen (HLA) alleles conferred protective effects in GW veterans based on lowered symptom severity. In a recent follow-up from this group (Engdahl et al, 2016), a difference in neural synchrony was found between ill and healthy GW veterans. In an important extension of these findings in the current issue, James et al (2016) integrate these “neuro” and immune components.…”
mentioning
confidence: 74%